Empowering Rural Communities through International Academic Collaboration: A Case Study of Trigona Honey Development and Digital Marketing in Salut Village, North Lombok, Indonesia - Lalu M. Furkan; Bao Yu; Ihsan Rois; Embun Suryani; Baiq Anggun Hilendri Lestari; Pahrul Azim (International Journal Of Community Service, 2024)
This study presents an international community service initiative implemented in Salut Village, North Lombok, Indonesia, through collaboration between the University of Mataram and Shangrao Normal University, China. The program aimed to empower local Trigona honey producers by enhancing their technical knowledge and equipping them with digital marketing skills. Employing a qualitative case study approach, the initiative combined experiential learning, cross-cultural engagement, and capacity-building strategies to promote sustainable rural development. Results indicate increased local knowledge, digital literacy, and entrepreneurial motivation. Despite challenges such as language barriers and limited infrastructure, the program demonstrated the transformative role of higher education institutions in fostering inclusive development through global academic partnerships. The study offers practical recommendations for sustaining impact and serves as a replicable model for university-led rural innovation initiatives aligned with the Sustainable Development Goals.